The Efficacy and Harms of Pharmacological Interventions for Aggression After Traumatic Brain Injury—Systematic Review - Hicks, Amelia J.; Clay, Fiona J.; Hopwood, Malcolm; James, Amelia C.; Jayaram, Mahesh; Perry, Luke A.; Batty, Rachel; Ponsford, Jennie L. (Frontiers in Neurology, 2019)
Background: Aggression is a commonly reported problem following traumatic brain injury (TBI). It may present as verbal insults or outbursts, physical assaults and/or property destruction. Aggressive behavior can fracture relationships and impede participation in treatment as well as a broad range of vocational and social activities, thereby reducing the individual’s quality of life. Pharmacological intervention is frequently used to control aggression following TBI. The aim of this systematic review was to critically evaluate the evidence regarding efficacy of pharmacological interventions for aggression following TBI in adults. Methods: We reviewed studies in English, published before December 2018. MEDLINE, PubMed, CINAHL, EMBASE, PsycINFO and CENTRAL databases were searched, with additional searching of key journals, clinical trials registries and international drug regulators. The primary outcomes of interest were reduction in the severity of aggression and occurrence of harms. The secondary outcomes of interest were changes in quality of life, participation, psychological health (e.g. depression, anxiety) and cognitive function. Evidence quality was assessed using the Cochrane Risk of Bias tool and the Joanna Briggs Institute Critical Appraisal Instruments. Results: Ten studies were identified, including five randomized controlled trials (RCTs) and five case series. There were positive, albeit mixed, findings for the RCTs examining the use of amantadine in reducing irritability (n=2) and aggression (n=2). There were some positive findings favouring methylphenidate in reducing anger (n=1). The evidence for propranolol was weak (n=1). Individual analysis revealed differential response to drug across individuals for both methylphenidate and propranolol. The less rigorous studies administered carbamazepine (n=2), valproic acid (n=1), quetiapine (n=1) and sertraline (n=1), and all reported reductions in aggression. However, given the lack of a control group it is difficult to discern treatment effects from natural change over time. Conclusions: This review concludes that a recommendation for use of amantadine to treat aggression and irritability in adults following TBI is appropriate. However, there is a need for further well-designed, adequately powered and controlled studies of pharmacological interventions for aggression following TBI.